2019
DOI: 10.1016/j.dadm.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cognitive impairment and retinal neural loss assessed by swept‐source optical coherence tomography in patients with mild cognitive impairment

Abstract: Introduction We compared peripapillary retinal nerve fiber layer and macular thickness measurements in patients with mild cognitive impairment (MCI) and control subjects using swept‐source optical coherence tomography (SS‐OCT). We also assessed the relationship between SS‐OCT measurements and the severity of cognitive impairment. Methods Peripapillary retinal nerve fiber layer and macular thickness were measured in 23 patients and 24 control subjects using SS‐OCT. Cognitive status was assessed using the Mini‐M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Two of the five studies showed pRNFL thinning, but no changes in the GCL-IPL complex or the macular volume (subjects MCI:controls, 52:101) (25,36). In the three other studies revealing significant differences, the authors observed significant thinning of macular structures in MCI patients compared with controls, but no significant differences in the pRNFL (subjects MCI:Controls, 90:168) (30,31,40). The final two studies did not find any significant changes in either pRNFL of macular structures between MCI patients and control pRNFL (subjects MCI:controls, 36:52) (39,45).…”
Section: Studies With Macular and Circumpapillary Oct Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Two of the five studies showed pRNFL thinning, but no changes in the GCL-IPL complex or the macular volume (subjects MCI:controls, 52:101) (25,36). In the three other studies revealing significant differences, the authors observed significant thinning of macular structures in MCI patients compared with controls, but no significant differences in the pRNFL (subjects MCI:Controls, 90:168) (30,31,40). The final two studies did not find any significant changes in either pRNFL of macular structures between MCI patients and control pRNFL (subjects MCI:controls, 36:52) (39,45).…”
Section: Studies With Macular and Circumpapillary Oct Resultsmentioning
confidence: 91%
“…Communication with the authors was attempted, but no clarification was possible ( 42 , 43 ). Finally, a total of 15 studies meeting inclusion criteria were evaluated and summarized ( 21 , 23 , 25 , 26 , 28 32 , 34 , 36 40 ) (see Figure 1 ). The general description and main findings of the included studies are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations